Regulasi Tekanan Darah pada Penderita Hipertensi Primer dengan Smoothie Pisang (Musa Paradisiaca) - Eni Puji Lestari; Abu Bakar; Laily Hidayati (Jurnal Ners, 2011)
Introduction: Hypertension is a major problem that often happen in Indonesia. Hypertension can cause many complications. In Indonesia almost patients with hypertension got farmacologic therapy, but there is no difference. Banana smoothie is one of nonfarmacologic therapy that can be used to lower blood pressure. The purpose of this study was to analyze the effect of banana smoothie on regulation in patients with primary hypertension.Method: This study used quasy experimental design. The population in this study were patients with primary hypertension in Kedungturi village Taman Sidoarjo. The sampling technique used nonprobability sampling type of purposive sampling. The total number of sample were 16 respondents who were selected based on inclusion and exclusion criteria.Result:The Result of paired t-test at the systolic blood pressure and diastolic blood pressure in experiment group showed p value = 0.000. Independent t test between experiment group post-test and control group post-test showed p value = 0.000 for systolic blood pressure and p value = 0.002 for diastolic blood pressure. This result showed that there was a difference value of pretest and post-test systolic and diastolic blood pressure. With the result of independen t-test we know that there is a difference value between exsperiment and control blood pressure.Discussion: This study explain that there was significant effect of banana smoothie to regulate blood pressure in patients with primary hypertention. Banana smoothie can regulate the blood pressure because of high kalium substance. The function of kalium is to reduce the effect of natrium so the blood pressure can down. It can be conclude that banana smoothie can regulate the blood pressure in patients with primary hypertention. In further day patients with hypertension can choose banana smoothie to regulate their blood pressure.